Ginkgolide With Intravenous Alteplase Thrombolysis in Acute Ischemic Stroke Improving Neurological Function: A Multicenter, Cluster-Randomized Trial (GIANT) - Zhang, Xuting; Zhong, Wansi; Ma, Xiaodong; Zhang, Xiaoling; Chen, Hongfang; Wang, Zhimin; Lou, Min; GIANT Investigators; Bi, Yong; Cai, Xueli; Cheng, Chaochan; Gu, Qun; et al. (Frontiers in Pharmacology, 2021)
Background and Purpose: We aimed to investigate the effect of Ginkgolide® treatment on neurological function in patients receiving intravenous (IV) recombinant tissue plasminogen activator (rt-PA). Methods: This study included acute ischemic stroke patients in 24 centers randomized to intervention of intravenous Ginkgolide® or control group within the first 24 hours after IV rt-PA therapy (IVT). Clinical outcome at 90 days was assessed with modified Rankin Scale (mRS) score and dichotomized into good outcome (0-2) and poor outcome (3-6). Hemorrhagic transformation represented the conversion of a bland infarction into an area of hemorrhage by computed tomography. Symptomatic intracerebral hemorrhage (sICH) was defined as cerebral hemorrhagic transformation in combination with clinical deterioration of National Institutes of Health Stroke Scale (NIHSS) score ≥4 points at 7-day or if the hemorrhage was likely to be the cause of the clinical deterioration. We performed logistic regression analysis and propensity score matching analysis to investigate the impact of Ginkgolide® treatment with IV rt-PA on good outcome, hemorrhagic transformation and sICH, respectively. Results: A total of 1113 patients were finally included and 513 (46.1%) were in the intervention group. Patients in the Ginkgolide® group were more likely to have good outcomes (78.6% vs 66.7%, p < 0.01) and lower rate of sICH (0 vs 2.72%, p < 0.01), compared with patients in the control group. The intra-cluster correlation coefficient (ICC) for good outcome at 90 days was 0.033. Binary logistic regression analysis revealed that treatment with Ginkgolide® was independently associated with 90-day mRS in patients with IV rt-PA therapy (OR 1.498; 95% CI 1.006-2.029, p = 0.009). After propensity score matching, conditional logistic regression showed intervention with Ginkgolide® was significantly associated with 90-day good outcome (OR 1.513; 95% CI 1.073 - 2.132, p = 0.018). No significant difference in hemorrhage transformation was seen between the 2 matched cohorts (OR 0.885; 95% CI 0.450-1.741, p = 0.724). Conclusions: Using Ginkgolide® within 24-hour after IV rt-PA is effective and safe and might be recommended in combination with rtPA therapy in acute ischemic stroke.